THE STUDENTS’ EYESIGHT: THE EFFECTIVENESS OF LEARNING-BASED APPLICATIONS ON ELT IN PANDEMIC ERA - Andi Bulkis Maghfirah Mannong (Universitas Islam Negeri Alauddin Makassar, 2020)
The emergence of the Covid-19 has given a significant effect that inflicted policy changes in various sectors, including in the education field. The most basic policy is changing the students’ way to learn from what is usually done in the classroom (face to face) to online learning. As this condition, the implementation of learning-based applications has a necessary role in supporting online learning, includes English Language Teaching (ELT). This study aimed to analyze the students’ experience in utilizing learning-based applications in learning English and the barriers faced by them. As for some of the applications most commonly used are Zoom, Google Meet, Google Classroom, and WhatsApp. Besides, this study was also conducted to determine which application is the most effective used in ELT during online learning. This research used descriptive quantitative, where the sample was the seventh-semester students in the English department at one of the private universities in Makassar. The data was collected used questionnaire and the data analysis technique used descriptive statistics. The result of this study showed that the use of those four applications helped the students to adapt to the pandemic condition. Besides helping students to learn English virtually, it also improves the students’ digital literacy. Although, there were some obstacles in utilizing some applications faced by them, such as limited quota, unstable network, complicated in use, and not focus during the learning process. Among the four applications above, the most effective application based on the students’ response was Whatsapp. This application helps the students to develop their language proficiency through natural interaction. Moreover, it makes the students easier in learning English as the delivery of material is systematic and structured. Students also have more time to understand the material by rereading the material that has been delivered.